MWH's water treatment principles and design - Crittenden, John C. (John Charles), 1949-; Borchardt, James H. (John Wiley & Sons, 2012)
"Updating the most comprehensive and complete guide to water treatment planning and design, this edition maintains the book's broad scope and reach, while reaching the working professional with additional worked problems and new treatment approaches. It covers both the principles and theory of water treatment as well as the practical considerations of plant design and distribution. The contents have been updated to cover changes to regulatory requirements, testing methodology, and design approaches, as well as the emergent topics of pharmacological agents in the water supply and treatment strategies"--